2020
DOI: 10.1007/s10854-020-02906-w
|View full text |Cite
|
Sign up to set email alerts
|

Graphene oxide-doped PEDOT:PSS as hole transport layer in inverted bulk heterojunction solar cell

Abstract: Transparent poly (3,4-ethylenedioxythiophene): poly (styrenesulfonate) (PEDOT:PSS) is widely used hole conducting material in optoelectronic devices. Secondary doping of PEDOT:PSS enables the tunability of its electronic properties. In this work, graphene oxide (GO) was used as a secondary dopant for PEDOT:PSS and the doped materials (composites) were tested for their efficiency as hole transport material in inverted bulk heterojunction (BHJ) solar cell. The composites were studied to unveil the effects of Cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 48 publications
0
6
0
Order By: Relevance
“…GO, a two-dimensional carbon material, has also been investigated to modified PEDOT:PSS as hole-transport materials in different OSCs. The Oleyamine-functionalized GO/PEDOT:PSS layer on PBDB-T:ITIC [ 317 ], PEDOT:PSS treated with GO layers on PTB7:PC 71 BM devices [ 318 ], on P3HT:PC 60 BM devices [ 319 ], on P3HT:PCBM devices [ 320 ], on inverted P3HT:PCBM OSCs [ 321 ], on inverted P3HT:PC 71 BM OSCs [ 322 ], and on reduced GO-germanium QDs modified PEDOT:PSS on P3HT:PCBM [ 323 ]. Raj et al reported the fabrication of PTB7:PC 70 BM-based OSCs with PEDOT:PSS:GO, resulting in enhanced PCE of 7.68% [ 324 ].…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
“…GO, a two-dimensional carbon material, has also been investigated to modified PEDOT:PSS as hole-transport materials in different OSCs. The Oleyamine-functionalized GO/PEDOT:PSS layer on PBDB-T:ITIC [ 317 ], PEDOT:PSS treated with GO layers on PTB7:PC 71 BM devices [ 318 ], on P3HT:PC 60 BM devices [ 319 ], on P3HT:PCBM devices [ 320 ], on inverted P3HT:PCBM OSCs [ 321 ], on inverted P3HT:PC 71 BM OSCs [ 322 ], and on reduced GO-germanium QDs modified PEDOT:PSS on P3HT:PCBM [ 323 ]. Raj et al reported the fabrication of PTB7:PC 70 BM-based OSCs with PEDOT:PSS:GO, resulting in enhanced PCE of 7.68% [ 324 ].…”
Section: Hole-transporting Materials As Htls In Oscsmentioning
confidence: 99%
“…There are many alternatives to PEDOT:PSS, but graphene oxide (GO) is utilized as its alternative in this simulation. All simulation parameters for HTM layers in the structure are carefully chosen from the reported experimental data and different works available in the literature [ 35 , 36 , 37 , 40 , 41 , 66 , 67 ].…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, PEDOT:PSS/GO exhibits a PCE of 12.34%—nearly equal to PEDOT:PSS—but their current density values differ. PEDOT:PSS/GO has a slightly different J-V curve than the other HTMs because it has distinct values for charge carrier mobilities, conductivity, and bandgap [ 35 , 67 ]. Due to this, it may interact differently with the light-harvesting layer.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…32,33 S. Ozcan et al reported using GO-doped PEDOT:PSS as an HTL in inverted bulk heterojunction of P3HT:PC 61 BM solar cell, which improved the device efficiency from 2.69 to 2.75%. 34 On the other hand, S. Rafique et al reported using a GO/PEDOT:PSS double-decked layer as HTL for PCDTBT:PC 71 BM solar cells, which led to a PCE of 4.28%; in comparison, GO or PEDOT:PSS HTLs on their own achieved PCEs of 2.77 and 3.57%, respectively. 23 The addition of GO to PEDOT:PSS for use as an HTL in a device architecture to be ITO/PEDOT:PSS:GO/PTB 7 :PC 71 BM/Al scored a PCE of 5.22%.…”
Section: Introductionmentioning
confidence: 99%